2004
DOI: 10.1007/s11103-004-0904-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Mal d 1-related genes in Malus

Abstract: It has been suggested that there are at least 15 Mal d 1-related (PR10) genes in one genotype of apple (Malus x domestica Borkh). We sequenced cDNA libraries of cultivar 'Royal Gala' and identified 12 members of the Mal d 1 family, including the previously reported Mal d 1b and Mal d 1d, an allelic variant of the previously reported Mal d 1a. Eight Mal d 1 gene products were expressed in tree-ripened fruit, in either the cortex or the skin, and most of these were also expressed in leaves in response to challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 65 publications
(108 reference statements)
6
51
0
3
Order By: Relevance
“…By Clustal W alignment, all Mal d 1 coding sequences in the database could be classified to these four subfamilies and members (Table 2). Subfamily I includes reference sequences that were formerly classified as Mal d 1a, Mal d 1b, Mal d 1c (Son et al 1999), and Mal d 1 d (Beuning et al 2004) isoforms or as PR-10a and PR-10c proteins (Ziadi et al 2001). The new sequences of this subfamily were derived from the PCR primer pairs 1 and 2 (Table 1) (Table 1), which not only represent all the reference sequences, but also include some new members.…”
Section: Generating and Grouping Mal D 1 Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…By Clustal W alignment, all Mal d 1 coding sequences in the database could be classified to these four subfamilies and members (Table 2). Subfamily I includes reference sequences that were formerly classified as Mal d 1a, Mal d 1b, Mal d 1c (Son et al 1999), and Mal d 1 d (Beuning et al 2004) isoforms or as PR-10a and PR-10c proteins (Ziadi et al 2001). The new sequences of this subfamily were derived from the PCR primer pairs 1 and 2 (Table 1) (Table 1), which not only represent all the reference sequences, but also include some new members.…”
Section: Generating and Grouping Mal D 1 Sequencesmentioning
confidence: 99%
“…The presence of Mal d 1.05 on LG 6 is unexpected, but its mapping is based on two reliable SNAP markers for the specific allele of FS. Two additional Mal d 1-related genes, Mal d 1m (AY428588) and Mal d 1n (AY428589) described by Beuning et al (2004), were not covered, because these sequences were not available at the time of our study. A DNA phylogenetic tree analysis indicated that Mal d 1m belongs to subfamily II, but is distinct from both including the residue S112, which is essential for IgE binding and cross-reactivity (Son et al 1999).…”
Section: Mal D 1 Gene Family Organization and Evolutionary Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all of these members are likely to be involved in allergenicity since only a limited number of different Mal d 1 proteins and mRNAs have been traced back in apple fruit so far (Helsper et al, 2002;Puehringer et al, 2003;Beuning et al, 2004).…”
Section: Resultsmentioning
confidence: 99%